PENERAPAN SUBSTITUSI PESTISIDA SINTETIS-BIOPESTISIDA PADA BUDIDAYA SAYURAN DI KELOMPOK TANI MAKMUR JAYA, KECAMATAN RASAU JAYA - Danie Indra Yama; Zaenal Mutaqin; Muliani; Rista Delyani; Tika Rahma Yunita; Muhammad Ali; Ragil Putri Widyastuti; Okto Ivansyah; Donor Utomo Muhammad Susilo; Agato; Muhammad Rizal; Dwi Isyana Achmad; Kirana Fadhilah; Erwan; Loko Jeremia Sembiring; Maida Solfianti; Ahul Saputra; Kasianus Tomi; Aryan Rahmad Abdillah Abdillah (LPPM Universitas Abdurrab, 2025)
Makmur Jaya Farmers Group is a partner of this PKM program.Teh group still relies on synthetic pesticides and traditional pest control methods due to limited trust in biopesticides. They also lack understanding of vegetable cultivation techniques based on the substitution of synthetis pesticides with biopesticides usingthe 6T principles, have limited skills in proper pesticide application, and require adequate spraying equipment. This PKM activity aims to shift the farmers mindset toward biopesticides, provide knowledge on vegetable cultivation through synthetic to biopesticide substitution appling the 6T principles, enhance their pesticide application skills and provide spraying equipment as assistance. The program began with a needs assessment, followed by socialization, training sessions, hand on practice in environmentally friendly pest and disease control, and the handover of donated sprayers. As aresult, the famers knoeledge and skills in eco-friendly OPT management significantly improved. Participans showed great enthusiasm and expressed commitment to transition from chemical pesticides to biopesticides.